Toni Morrison’s Home: an Ecolingustic Analysis - Das, Shruti; Chanda, Naba Kumar (Literary Studies, 2023)
Since the publication of Arran Stibbe's critically acclaimed book Ecolinguistics: Language, Ecology, and the Stories We Live By (2015), a new approach to ecolinguistics has emerged, one that focuses on how much ecologically constructive or destructive views are included in the discourses contained in the "stories" that people "live by" every day. Toni Morrison, expanding the possibilities of African American ecological writing, explores the healing impact of nature that is reflected in the "stories" the characters "live by" in her novels. Her writings build a narrative frame in which nature is the benefactor and healer. On the one hand the narratives poignantly and painfully expose the psychological or emotional wounds suffered by the African- Americans and on the other depict nature as a healer of these wounds. Our concern in this paper is Morrison’s novel Home (2012). It is a story of a veteran soldier, Frank Money who returns home, with traumatic war memories deeply entrenched into his mind, to rescue his sister Cee from the clutches of a doctor who was abusing her body. The siblings are ultimately healed by associating themselves with and communicating with other members of their community and nature. This paper will apply Stibbe’s theory of ecolinguistics and look at the stories and narrative discourses in Morrison’s Home to see how the ecology of language in the narrative posits that living in harmony with nature produces a healing effect.